Trend and Seasonality Analysis on International Shrimp Market Prices Exported from Andhra Pradesh, India - Rajani, M.; Balasubramanian, A. (Fishery Technology, 2025)
Shrimp remains one of the most traded food items worldwide, and its farming is an important activity in various maritime states of India. Shrimp prices experience uncertain fluctuations caused by changes in market demands, domestic and export demands. These undulations in market price impact the national economy. Owing to this, the study was designed with the objective to analyse the trends and seasonal changes in shrimp market prices, by collecting monthly shrimp price data from various published sources like MPEDA statistics and field offices of MPEDA from January 2020 to December 2023. The shrimp were categorized into count price grades, ranging from 30 to 70 Count (C) per kg. The analysis revealed that, over the long term, shrimp prices for the 40 C to 70 C grades in the Andhra Pradesh export market showed an insignificant upward trend. Monthly price variability in Andhra Pradesh showed that size grade 30C had the lowest variability in June, while the size grade 50C had the highest variability in April. The study also revealed that the seasonal indices in shrimp prices were highest in the month of January for all shrimp count size grades (30 to 70C per Rs./kg) and lowest in April (40 to 70 C per Rs./kg) and in July (30C per Rs./kg) in the Andhra Pradesh export market.